The clinical profile, etiology and short term outcome of neonatal seizures at Patan Hospital, Nepal - Kansakar, Prerana (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: The incidence of seizure is as high as 5/1000 live births and the mortality rate can be up to 15%. So this study was conducted to find out the clinical profile, causes and immediate outcome of neonatal seizures at Patan Hospital. Methods: In this retrospective study, all neonates (aged 0-28 days) with seizure admitted to Patan Hospital over a period of one year from January 2015 to December 2015 were included. The data were obtained from hospital records and analyzed using SPSS 12. Results: There were 32 cases of neonatal seizures admitted over the period of one year out of which 23 were born at Patan Hospital. The incidence of neonatal seizure was 2.9 cases of per 1000 live birth. Among neonates with seizure, 63% were male, 81% were term and 69% were of birth weight more than 2500gm. The cause of seizure was hypoxic ischemic encephalopathy in 25% of cases and no cause could be found in 15% of cases. Phenobarbitone alone controlled seizure in more than 50% of cases. The mortality rate was 9.3% with hypoxic ischemic encephalopathy being the most common cause. Conclusion: The most common cause of neonatal seizure is hypoxic ischemic encephalopathy and is also the leading cause of death in neonates with seizure. Therefore improvement in healthcare during the delivery of newborns can decrease the incidence and death due to neonatal seizure.